2014
DOI: 10.1007/s10552-014-0441-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium

Abstract: Purpose It has been suggested that parental occupational paint exposure around the time of conception or pregnancy increases the risk of childhood leukemia in the offspring. Methods We obtained individual level data from 13 case-control studies participating in the Childhood Leukemia International Consortium (CLIC). Occupational data were harmonized to a compatible format. Meta-analyses of study-specific odds ratios (ORs) were undertaken, as well as pooled analyses of individual data using unconditional logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
0
21
1
2
Order By: Relevance
“…For childhood leukaemia, The majority of more recent studies have also reported increased risks associated with benzene-related occupational exposures, either for paternal (Feychting et al 2001;Metayer et al 2016;Miligi et al 2013;Reid et al 2011) or maternal exposure (Infante-Rivard et al 2005;McKinney et al 2008;Miligi et al 2013;Reid et al 2011;Schuz et al 2000;Shu et al 1999). However, two large recent studies (Bailey et al 2014;Keegan et al 2012), including a study of 5 the Childhood Leukaemia International Consortium (CLIC) focusing on parental occupational exposure to paint (Bailey et al 2014), found no evidence of an association. Most previous studies looked at broad occupational or substance groups while only a minority considered exposure to benzene specifically.…”
Section: Introductionmentioning
confidence: 99%
“…For childhood leukaemia, The majority of more recent studies have also reported increased risks associated with benzene-related occupational exposures, either for paternal (Feychting et al 2001;Metayer et al 2016;Miligi et al 2013;Reid et al 2011) or maternal exposure (Infante-Rivard et al 2005;McKinney et al 2008;Miligi et al 2013;Reid et al 2011;Schuz et al 2000;Shu et al 1999). However, two large recent studies (Bailey et al 2014;Keegan et al 2012), including a study of 5 the Childhood Leukaemia International Consortium (CLIC) focusing on parental occupational exposure to paint (Bailey et al 2014), found no evidence of an association. Most previous studies looked at broad occupational or substance groups while only a minority considered exposure to benzene specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have reported associations between parental occupational exposures to solvents, paints, pigments, pesticides, lead, combustion exhaust and the risk of childhood leukemia (Infante-Rivard et al, 2005; McKinney et al, 2008; Reid et al, 2011; Van Maele-Fabry et al., 2011; Vinson et al, 2011; Wigle et al, 2009). Most studies relied on job titles lacking specificity for type and intensity of exposure, and/or had a small sample size (Colt and Blair, 1998; Van Maele-Fabry et al, 2011; Vinson et al, 2011; Wigle et al, 2009; Keegan et al, 2012; Bailey et al, 2014a, 2014b). Few studies used expert occupational exposure assessment (Infante-Rivard et al, 2005; McKinney et al., 2008; Reid et al, 2011; Monge et al, 2007; Perez-Saldivar et al, 2008; Miligi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The focus of these analyses was to investigate home paint exposure in relation to ALL. We have previously published findings of pooled analyses investigating parental occupational exposure to paints and the risk of childhood ALL using data from CLIC studies and found no association with paternal occupational exposure around conception, but had insufficient statistical power to investigate maternal occupational exposure during pregnancy (3). …”
Section: Introductionmentioning
confidence: 99%